The influence of phthalocyanine aggregation in complexes with CdSe/ZnS quantum dots on the photophysical properties of the complexes - Martynenko, Irina V.; Orlova, Anna O.; Maslov, Vladimir G.; Fedorov, Anatoly V.; Berwick, Kevin; Baranov, Alexander V. (Beilstein Journal of Nanotechnology, 2016)
The formation of nonluminescent aggregates of aluminium sulfonated phthalocyanine in complexes with CdSe/ZnS quantum dots causes a decrease of the intracomplex energy transfer efficiency with increasing phthalocyanine concentration. This was confirmed by steady-state absorption and photoluminescent spectroscopy. A corresponding physical model was developed that describes well the experimental data. The results can be used at designing of QD/molecule systems with the desired spatial arrangement for photodynamic therapy.
Keywords: aggregation; Förster resonance energy transfer; photosensitizer; semiconductor nanocrystals; tetrapyrroles

(untitled) - Blas-Ferrando, V. M.; Ortiz, J.; González-Pedro, V.; Sánchez, R. S.; Mora-Seró, I.; Fernández-Lázaro, F.; Sastre-Santos, A. (Chem. Commun., 2015)

(untitled) - Dayneko, S.; Tameev, A.; Tedoradze, M.; Martynov, I.; Artemyev, M.; Nabiev, I.; Chistyakov, A. (Appl. Phys. Lett., 2013)

(untitled) - Saha, S. K.; Guchhait, A.; Pal, A. J. (J. Appl. Phys., 2012)

(untitled) - Medintz, I. L.; Mattoussi, H. (Phys. Chem. Chem. Phys., 2009)

(untitled) - Martynenko, I. V.; Kuznetsova, V. A.; Orlova, A. O.; Kanaev, P. A.; Maslov, V. G.; Loudon, A.; Zakharov, V. V.; Parfenov, P. S.; Gun’ko, Y. K.; Baranov, A. V.; Fedorov, A. V. (Nanotechnology, 2015)

(untitled) - Shibu, E. S.; Hamada, M.; Murase, N.; Biju, V. (J. Photochem. Photobiol., C: Photochem. Rev., 2013)

(untitled) - Lemon, C. M.; Karnas, E.; Bawendi, M. G.; Nocera, D. G. (Inorg. Chem., 2013)

(untitled) - Li, F.; He, Z.; Li, M.; Zhang, J.; Han, J.; Lu, P. (Mater. Lett., 2014)

(untitled) - Valanciunaite, J.; Skripka, A.; Araminaite, R.; Kalantojus, K.; Streckyte, G.; Rotomskis, R. (Chemija, 2011)

(untitled) - Zenkevich, E. I.; Gaponenko, S. V.; Sagun, E. I.; von Borczyskowski, C. (Rev. Nanosci. Nanotechnol., 2013)

(untitled) - Sharman, W. M.; Allen, C. M.; van Lier, J. E. (Drug Discovery Today, 1999)

Optical Properties of Semiconductor Nanocrystals - Gaponenko, S. V. (Cambridge University Press, 1998)

Optical Properties of Semiconductor Quantum Dots - Fedorov, A. V.; Rukhlenko, I. D.; Baranov, A. V.; Kruchinin, S. Y. (Nauka, 2011)

Semiconductor Nanocrystals: From Basic Principles to Applications - Efros, A. L.; Lockwood, D. J.; Tsybeskov, L. (Springer, 2003)

(untitled) - Clapp, A. R.; Medintz, I. L.; Mauro, J. M.; Fisher, B. R.; Bawendi, M. G.; Mattoussi, H. (J. Am. Chem. Soc., 2004)

(untitled) - Orlova, A. O.; Martynenko, I. V.; Maslov, V. G.; Fedorov, A. V.; Gun’ko, Y. K.; Baranov, A. V. (J. Phys. Chem. C, 2013)

(untitled) - Beane, G.; Boldt, K.; Kirkwood, N.; Mulvaney, P. (J. Phys. Chem. C, 2014)

(untitled) - Zenkevich, E. I.; Blaudeck, T.; Milekhin, A.; von Borczyskowski, C. (Int. J. Spectrosc., 2012)

(untitled) - Martynenko, I. V.; Orlova, A. O.; Maslov, V. G.; Baranov, A. V.; Fedorov, A. V.; Artemyev, M. (Beilstein J. Nanotechnol., 2013)

(untitled) - Valanciunaite, J.; Klymchenko, A. S.; Skripka, A.; Richert, L.; Steponkiene, S.; Streckyte, G.; Mely, Y.; Rotomskis, R. (RSC Adv., 2014)

(untitled) - Rotomskis, R.; Valanciunaite, J.; Skripka, A.; Steponkiene, S.; Spogis, G.; Bagdonas, S.; Streckyte, G. (Lith. J. Phys., 2013)

(untitled) - Oluwole, D. O.; Britton, J.; Mashazi, P.; Nyokong, T. (Synth. Met., 2015)

(untitled) - Kilin, D. S.; Tsemekhman, K.; Prezhdo, O. V.; Zenkevich, E. I.; von Borczyskowski, C. (J. Photochem. Photobiol., A: Chem., 2007)

(untitled) - Blaudeck, T.; Zenkevich, E. I.; Abdel-Mottaleb, M.; Szwaykowska, K.; Kowerko, D.; Cichos, F.; von Borczyskowski, C. (ChemPhysChem, 2012)

(untitled) - Zenkevich, E. I.; Stupak, A. P.; Kowerko, D.; von Borczyskowski, C. (Chem. Phys., 2012)

(untitled) - Orlova, A. O.; Maslov, V. G.; Baranov, A. V.; Gounko, I.; Byrne, S. (Opt. Spectrosc., 2008)

European Conference on Biomedical Optics, International Society for Optics and Photonics - Martynenko, I.; Visheratina, A.; Kuznetsova, V.; Orlova, A.; Maslov, V.; Fedorov, A.; Baranov, A. (Quantum dot-tetrapyrrole complexes as photodynamic therapy agents, Munich, Germany, 21.6.2015-25.6.2015, 2015)

(untitled) - McArthur, E. A.; Godbe, J. M.; Tice, D. B.; Weiss, E. A. (J. Phys. Chem. C, 2012)

(untitled) - Halpert, J. E.; Tischler, J. R.; Nair, G.; Walker, B. J.; Liu, W.; Bulović, V.; Bawendi, M. G. (J. Phys. Chem. C, 2009)

(untitled) - Camp, P. J.; Jones, A. C.; Neely, R. K.; Speirs, N. M. (J. Phys. Chem. A, 2002)

(untitled) - Kuznetsova, N. A.; Gretsova, N. S.; Derkacheva, V. M.; Kaliya, O. L.; Lukyanets, E. A. (J. Porphyrins Phthalocyanines, 2003)

(untitled) - Palewska, K.; Sworakowski, J.; Lipiński, J. (Opt. Mater., 2012)

(untitled) - Palewska, K.; Sworakowski, J.; Lipiński, J.; Nešpůrek, S. (J. Photochem. Photobiol., A: Chem., 2011)

(untitled) - Petrášek, Z.; Phillips, D. (Photochem. Photobiol. Sci., 2003)

(untitled) - Yu, W. W.; Qu, L.; Guo, W.; Peng, X. (Chem. Mater., 2003)

Delocalized Excitation and Excitation Transfer - Förster, T. (Florida State University, 1965)

(untitled) - Zhang, X.; Liu, Z.; Ma, L.; Hossu, M.; Chen, W. (Nanotechnology, 2011)

Principles of Fluorescence Spectroscopy - Lakowicz, J. R. (Springer, 2006)

(untitled) - Ogunsipe, A.; Chen, J.-Y.; Nyokong, T. (New J. Chem., 2004)

(untitled) - Oluwole, D. O.; Nyokong, T. (Polyhedron, 2015)

(untitled) - Idowu, M.; Chen, J.-Y.; Nyokong, T. (New J. Chem., 2008)

(untitled) - Apolikhin, O. I.; Chemishov, I. V.; Sivkov, A. V.; Altunm, D. V.; Kuzmin, S. G.; Vorozhtsov, G. N. (Proc. SPIE, 2007)

Fundamentals of Analytical Chemistry - Skoog, D. A. (Thomson-Brooks, 2004)

(untitled) - Talapin, D. V.; Rogach, A. L.; Kornowski, A.; Haase, M.; Weller, H. (Nano Lett., 2001)

(untitled) - Kubin, R. F.; Fletcher, A. N. (J. Lumin., 1982)